Gender equality and digital counter-publics in global Buddhism: bhikkhuni ordination in the Thai Forest Tradition in Australia. Issue 1 (2nd January 2022) - Halafoff, Anna; Tomalin, Emma; Starkey, Caroline
ABSTRACT: Gender discrepancies persist in Buddhist societies and institutions, linked to cultural and religious beliefs and practices that allocate a lower status to women. In some Buddhist traditions, nuns cannot ordain to the same level as monks, most Buddhist archetypes of enlightenment remain male, and men hold positions of power and privilege within the majority of Buddhist organisations. This article focuses on recent controversy surrounding bhikkhuni ordination in the Thai Forest Tradition in Australia and the role of the Internet in these debates. The authors draw on data collected in interviews with key figures in Buddhism in Australia, including Venerable Chi Kwang Sunim, Ayya Nirodha, Ajahn Brahmavamso Mahathera, and Bhante Sujato, recorded as part of the "Buddhist Life Stories of Australia" research project. We argue that the international Buddhist women's movement and its allies are creating and using digital counter-publics to advance gender parity in contemporary Buddhism. Online activism has not only accelerated the pace of progressive social change, but it has also been used by more conservative actors to try to thwart these changes and maintain their authority, although less successfully.